The criminology of place : street segments and our understanding of the crime problem - Weisburd, David; Groff, Elizabeth (Elizabeth R.); Yang, Sue-Ming. (Oxford ; New York : Oxford University Press, 2012)
Based on a 16-year longitudinal study of crime in Seattle, Washington.
Includes bibliographical references (p. [237]-264) and indexes..
Keywords: Crime -- Environmental aspects; Geographical offender profiling; Criminal behavior, Prediction of; Crime scenes; Crime analysis; Crime prevention; Crime analysis; Crime -- Environmental aspects; Crime prevention; Crime scenes; Criminal behavior, Prediction of; Geographical offender profiling